Priredba vprašalnika South Oaks gambling screen za slovensko kulturno okolje - Cvenkelj, Andreja (Psihološka obzorja (Ljubljana), 2010)
South Oaks Gambling Screen (Lesieur in Blume, 1987) is the most frequently used for screening of pathological gambling. The main purpose of this study was to adapt the SOGS for application in the Slovenian cultural environment and to assess its metric characteristics. The study involved 121 subjects, 21 of which were diagnosed as pathological gamblers. Comparison group was composed of 100 subjects. Factor analysis resulted in a one-dimensional solution accounting for 66% of the total variance. Statistically significant differences in the scores show that the SOGS is able to discriminate between the comparison group and pathological gamblers. Item analysis shows that all of them appropriately discriminate between pathological gamblers and comparison group. The internal consistency of the 20-item scale was .971. The criterion validity of the Slovenian version of the SOGS was investigated by cross-comparing the patients' actual diagnoses of pathological gambling with the same diagnoses based on the SOGS scores. The score of 5 points was used asa cut-off point, since it discriminates the most. There was a perfect agreement between diagnoses of pathological gambling and diagnoses based on the SOGS scores.
Keywords: igre na srečo; odvisnosti; psihološki testi; veljavnost; zanesljivost; diskriminativnost